Operation support system of power communication network based on cloud platform - Zhimin YANG; Danke HONG; Li WANG; Junyi XIE (Dianxin kexue)
Electric power communication network operation support system is a technical support system for daily dispatching and operation of communication network.Its safe and reliable operation is very important for the safe operation of communication network.A high availability architecture of power communication network operation support system based on cloud platform was presented,and its practice in power enterprises was introduced.Finally,the system high availability evaluation model and simulation results were given.The results show that the system architecture significantly improves the reliability of the system.